DESAIN INSTRUKSIONAL BIMBINGAN MINAT BACA BERBASIS HYPNOSIS BAGI CALON PUSTAKAWAN TENAGA AHLI (CPTA) - Agustina, Susanti (Edulib, 2017)
Instructional design of hypnosis-based reading interest guidance is the development of guidance material of reading interest that previously has been created by Perpustakaan Nasional Indonesia (National Library of Indonesia) for the training of Calon Pustakawan Tenaga Ahli (CPTA) or Expert Librarian Candidate. The development of learning design that combines theory and practice is absolutely needed. Moreover, the result of class survey signifies that only 10% of CPTA training participants are interested in reading. This instructional design employs MINERVA model since it aims to result instructional system directing to the formation of CPTA employability skill. The skill in bibliotherapy for CPTA in a college to guide reading interest is required, especially to boost the motivation and learning capacity of civitas academica, specifically librarian who experience stress symptom due to final project. The skill in bibliotherapy requires provision in effective reading capacity and efficient reading comprehension. Through the learning of hypnosis-based reading interest guidance, firstly CPTA participants can reflect the level of reading awareness, secondly be the support of bibliotherapy program in college library, and thirdly boost mental awareness. Librarian is not only limited to administrative service, but also it has role as vanguard in mental literacy service through bibliotherapy.